2019
DOI: 10.3390/w11102179
|View full text |Cite
|
Sign up to set email alerts
|

Hypolimnetic Hypoxia Increases the Biomass Variability and Compositional Variability of Crustacean Zooplankton Communities

Abstract: In freshwater lakes and reservoirs, climate change and eutrophication are increasing the occurrence of low-dissolved oxygen concentrations (hypoxia), which has the potential to alter the variability of zooplankton seasonal dynamics. We sampled zooplankton and physical, chemical and biological variables (e.g., temperature, dissolved oxygen, and chlorophyll a) in four reservoirs during the summer stratified period for three consecutive years. The hypolimnion (bottom waters) of two reservoirs remained oxic throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Many field observations indicated that the maximum zooplankton density during the day is usually in the top part of the metalimnion with a relatively high oxygen concentration [78][79][80][81]. Other field studies revealed that zooplankton could be found in high abundances in anoxic waters [2,23,82,83]. We observed similar patterns where the upper anoxic layers had a higher biomass of zooplankton and also a large proportion of large Cladocera.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Many field observations indicated that the maximum zooplankton density during the day is usually in the top part of the metalimnion with a relatively high oxygen concentration [78][79][80][81]. Other field studies revealed that zooplankton could be found in high abundances in anoxic waters [2,23,82,83]. We observed similar patterns where the upper anoxic layers had a higher biomass of zooplankton and also a large proportion of large Cladocera.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, inedible algae or cyanobacteria could be the main factor that favors small zooplankton species in these lakes because they are better competitors than large herbivorous filter-feeders in the presence of large inedible algae [62]. However, the dominance of Rotifera and small Cladocera could also be a result of oxygen stress, which may increase the presence and dominance of these taxa in zooplankton communities that are less sensitive to hypoxic conditions [2]. This is consistent with our results, which showed that most rotifers seemed to prefer low oxygen conditions, and the smaller Cladocera were more resistant to oxygen depletion than the larger daphnids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a typical year, BVR is stratified from mid‐March to late October and mixed from November to early March (Hounshell et al, 2021). BVR experiences summer hypolimnetic anoxia and cyanobacterial blooms, both of which are controlled by water temperature and thermal stratification (Doubek et al, 2019; Hamre et al, 2018), making forecasts of water temperature important for water quality management.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the presence of Cladocera decreased between years, but Cyclopoida disappeared with the highest trophic status observed in 2015. Variation in community structure alters ecosystem functioning and biodiversity metrics can indicate how communities influence ecosystems [101][102][103][104]. Seasonal and interannual increases in Daphnia abundance have been associated with P limitation due to higher requirements in Daphnia than in other taxa [105].…”
Section: Discussionmentioning
confidence: 99%